Respuesta :

Answer:

1 and 3

Step-by-step explanation:

Because when you multiply the powers

then the powers will be added together.

Answer:

6b^3(-2b^3)=-12b^6

3a^3(-3a^4)= -9a^7

Step-by-step explanation:

Equation 1: 6b^3(-2b^3)

multiplying: 6*(-2) b^3*b^3 = -12 b^(3+3) = -12b^6

Equation 2: 8x^3(3x^2)

multiplying: 8*3 x^3*x^2 = 24 x^(3+2) = 24x^5

Equation 3: 3a^3(-3a^4)

multiplying: 3*(-3) a^3*a^4 = -9 a^(3+4) = -9a^7

Equation 4: 4x^3(6x^2)

multiplying: 4*6 x^3*x^2 = 24 x^(3+2) = 24x^5